The Effectiveness of Digital-Based Marketing Science Teaching Innovation - B.M.A.S. Anaconda Bangkara; Eka Hendrayani; Cahyani Pratisti; Rudianto; Hermiyetti (Universitas Pendidikan Ganesha, 2023)
This research emerged in response to the challenge of improving students' academic success in marketing science. With the development of digital technology, digital-based teaching methods are considered as potential innovations to enrich the learning experience. The main objective of this study is to evaluate the effectiveness of digital-based teaching innovations. It includes understanding whether the use of digital tools and interactive methods enhances students' understanding of marketing science concepts and academic performance. This study is a case study that focuses on the implementation of digital-based teaching methods in a marketing science education environment. The research subjects involved students participating in digital-based marketing science classes at the Sultan Muhammad Syafiuddin Islamic Institute in Sambas. This research applies a combined approach between qualitative and quantitative through digital-based teaching using various digital tools such as multimedia presentations, interactive online platforms, and virtual simulations. The results of this case study show that digital-based marketing science teaching innovation has a positive impact. Students show high interest, active participation, increased understanding of concepts, and improved academic performance. Overall, this research supports the effectiveness of digital-based teaching in marketing science. The integration of digital tools and interactive methods can improve the quality of education and provide a more engaging learning environment for students.